2013
DOI: 10.1590/s0104-77602013000300015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water deficit and season on biomass yield from clonal stands of eucalyptus

Abstract: ABSTRACT:This study aimed to analyze the influence of different levels of water deficit (DH) on initial seedling development of six clonal stands of hybrid Eucalyptus grandis x E. urophylla in two seasons of the year. The experiment was conducted in the experimental site of UFES, in the municipality of Jerônimo Monteiro (ES), over two seasons: from February 9, 2009 to June 9, 2009 (season 1) and from July 11, 2009 to November 7, 2009. In all experimental treatments, the first 30 days consisted of acclimating s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…Similar results were also found by Sperandio et al (2010) for species of Eucalyptus grandis and Eucalyptus urophylla. Using hybrid species of Eucalyptus grandis x Eucalyptus urophylla, Tatagiba et al (2015) and Xavier et al (2013) concluded that high values of hydric deficit reduced the production of dry wood at the end of the eucalyptus productive process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were also found by Sperandio et al (2010) for species of Eucalyptus grandis and Eucalyptus urophylla. Using hybrid species of Eucalyptus grandis x Eucalyptus urophylla, Tatagiba et al (2015) and Xavier et al (2013) concluded that high values of hydric deficit reduced the production of dry wood at the end of the eucalyptus productive process.…”
Section: Resultsmentioning
confidence: 99%
“…According to Xavier et al (2013), eucalyptus crops are often established in locations with high atmospheric demand and sparse, irregular rates of annual rainfall, which endanger both the success and productivity of the crops. Therefore, the climatic zoning is an important tool for the delimitation of areas with climatic aptitudes for the planting and development of forest varieties, as established through climatic and hydrological indicators of the region.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Framptom & Foster (1993) os testes de espécies e procedências e os testes clonais têm sido usados para recomendar material genético para condições ambientais específicas. Trabalhos que demonstram o crescimento de diferentes genótipos de eucalipto têm sido desenvolvidos a fim de indicar clones mais adequados a diferentes condições ambientais (CHAVES et al,2004;VELLINI et al, 2008;XAVIER et al, 2013;TATAGIBA et al, 2015). Os resultados obtidos por estes autores têm auxiliado a tomada de decisão para recomendação de clones para áreas com diferentes condições de disponibilidade hídrica no solo, proporcionando vantagens como, maior produtividade, redução de custos na implantação do plantio e aumento na eficiência do Irriga, Botucatu, v. 21, n. 1, p. 104-118, janeiro-março, 2016 uso da água pelas plantas.…”
Section: Tatagiba S D; Pezzopane J E M; Vinco J S; Pinheirounclassified
“…Nestas mesmas condições atmosféricas e a 50% da AD, os clones 2, 3 e 4 apresentaram valores de área foliar significativamente semelhantes entre si, assim como aconteceu para os clones 1 e 2, enquanto os clones 3 e 4, registraram médias significativamente superiores em relação ao clone 1 (Figura 3f). Estes resultados estão de acordo com os observados por Xavier et al (2013) e Tatagiba et al (2015) que verificaram reduções de área foliar em procedências da mesma espécie do gênero Eucalyptus, submetidas à deficiência hídrica no solo. Blum (1997) ressalta que a diminuição da atividade fotossintética e da produtividade de plantas submetidas à deficiência hídrica tem grande correlação com a redução da área foliar.…”
Section: Caracterização Do Crescimento Dos Clones De Eucaliptounclassified